The permeable and the pervasive: Approaching an understanding of atmospheres of home among Tanzanian Indians - Cecil Marie Schou Pallesen (Ambiances)
What does it mean to be at home when your sense of belonging is ambivalent? What is home if the physical frames of what you call home are contested? And is it possible to grasp an atmosphere of a home’s firm, yet vulnerable qualities? For Tanzanian Indians, on whom this article focuses, the immediate boundaries of their dwelling are solid and materialised in heavy wooden doors and massive metal lattice doors with padlocks. The outside is kept at a distance but constantly imposes itself in different forms of materiality. Behind this lurks the anxiety sparked by the nationalisation of Indian houses that took place after Independence: many Tanzanian Indians are still fighting to regain ownership of their houses. Exploring experiences of permeability of the home, the article shows how different measures are taken by the inhabitants to prevent certain things entering the home, while openness to others is essential to creating a feeling of home. Permeability conveys and enables certain atmospheres of belonging and non-belonging. Based on long-term ethnographic fieldwork in an Indian migrant community in Tanzania and working with subtle details of everyday sensory and material practices in the home, the article explores how studying the atmosphere of home through permeability and the pervasive allows a closer understanding of the intimate politics of what it means to create and sustain a feeling of home as a marginalised but resourceful migrant minority.